Optimization of Therapy for Atopic Dermatitis in Young Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Atopic dermatitis in children is characterized by staged development, polymorphism of clinical manifestations and persistent recurrent course.One of the main tasks of treating atopic dermatitis is to prevent relapses of the disease, which is achieved by complex external proactive therapy.